Ground-based astrometry calibrated by Gaia DR1: new perspectives in asteroid orbit determination - Spoto, Federica; Altmann, Martin (Astronomy and astrophysics, 2017)
Data Release 1 (GDR1) is a first, important step on the path of evolution of astrometric accuracy towards a much improved situation. Although asteroids are not present in GDR1, this intermediate release already impacts asteroid astrometry.Aims. Our goal is to investigate how the GDR1 can change the approach to a few typical problems, including the determination of orbits from short-arc astrometry, the exploitation of stellar occultations, and the impact risk assessment.Methods. We employ optimised asteroid orbit determination tools, and study the resulting orbit accuracy and post-fit residuals. For this goal, we use selected ground-based asteroid astrometry, and occultation events observed in the past. All measurements are calibrated by using GDR1 stars.Results. We show that, by adopting GDR1, very short measurement arcs can already provide interesting orbital solutions, capable of correctly identifying near-Earth asteroids (NEAs) and providing a much more accurate risk rating. We also demonstrate that occultations, previously used to derive asteroid size and shapes, now reach a new level of accuracy at which they can be fruitfully used to obtain astrometry at the level of accuracy of Gaia star positions.